Analysis of Corrosion Causes in Metal Components and Prevention Strategies: A Case Study at PT Arqom Technology Innovation - Andrian Riyadi; Heru Tri Atmaja; Indra Nur Cahya (TURBO [Tulisan Riset Berbasis Online], 2026)
Corrosion is a critical material degradation issue that significantly affects the reliability and service life of metal components in the manufacturing industry. PT Arqom Technology Innovation faces corrosion problems in post-fabricated metal components influenced by working environment conditions and production processes. This study aims to analyze the dominant factors causing corrosion, identify the prevailing types of corrosion, and evaluate the effectiveness of the implemented corrosion prevention strategies through a case study at PT Arqom Technology Innovation. The research employed a descriptive-analytical approach based on field observations, visual inspection of components, interviews, and a review of technical documents and relevant literature. The results indicate that high relative humidity and welding processes are the primary factors accelerating material degradation, with localized pitting corrosion and galvanic corrosion predominantly occurring at welded joints and the Heat Affected Zone (HAZ). The existing surface protection strategy is considered inadequate for the level of environmental aggressiveness. This study highlights the need for improving post-fabrication processes, selecting appropriate coating systems, and implementing structured preventive maintenance to effectively control corrosion in a sustainable manner.